Specificity of L1 peptides versus virus-like particles for detection of human papillomavirus-positive cervical lesions in females attending Engativa Hospital, Bogota, Colombia (2008)
A serological test for the detection of human papillomavirus (HPV) infection in females at risk of developing cervical cancer could be based on conserved L1 peptides with low levels of antigenicity specifically recognized by antibodies from patients with cervical lesions infected with high-risk HPV (HR-HPV) types. The aim was to assess the ability of L1 peptides 18283, 18294, and 18301 compared with the ability of virus-like particles (VLPs) to identify these infections in females. A total of 391 HPV-infected female volunteers were interviewed, and peripheral blood and cervical cells were obtained for detection of anti-HPV antibodies and HPV DNA; all of the patients had a Pap smear test; 287 patients were referred for colposcopy or biopsy, according to gynecological criteria. The level of agreement, as determined by the use of the Lin coefficient (rho value), showed that 75 to 83% of females with HR-HPV DNA-positive cervical lesions had antibodies that recognized VLPs and peptide 18283, 18294, or 18301, while 15 to 23% of the HPV DNA-negative females with a normal cytology had antibodies that recognized these three peptides and 45% had antibodies that recognized VLPs. The rate of agreement between peptides and VLPs for antibody detection was higher for patients with HPV DNA-positive cervical lesions. Peptides 18283, 18294, and 18301 showed similar sensitivities for the detection of HR-HPV DNA-positive cervical lesions and were more specific than VLPs. Peptide 18301 might be detecting protective antibodies in HPV DNA-negative females with atypical squamous cells of undetermined significance. These peptides could be useful for the design of a serology test for the detection of HR-HPV infection in females with cervical lesions and at risk of cervical cancer.